Broadband Photodetector Based on Inorganic Perovskite CsPbBr3/GeSn Heterojunction. Issue 8 (23rd June 2021) - Cong, Hui; Chu, Xinbo; Wan, Fengshuo; Chu, Zema; Wang, Xiaoyu; Ma, Yao; Jiang, Jizhong; Shen, Liang; You, Jingbi; Xue, Chunlai
Abstract: Photodetectors with broadband response spectrum have attracted great interest in many application areas such as imaging, gas sensing, and night vision. Here, a high performance broadband photodetector is demonstrated with inorganic perovskite CsPbBr3 /GeSn heterojunction, detection range can be covered from 450 to 2200 nm. The responsivity of heterojunction device can achieve as high as 129 mA W −1 under illuminated light of 532 nm, which is 4.92 times larger than that of a GeSn based device. As the CsPbBr3 can also act as anti‐reflective coating for infrared wavelength, the infrared band responsivity at wavelength of 2200 nm can also be raised by 1.42 times. In addition, the device with all inorganic components is showed good stability, while keeping in the dry environment, the device can sustain its 90% original after 550 h storage. These results show the inorganic perovskite/GeSn heterojunction device is of great potential in broadband photodetection with high responsivity. Abstract : A high performance broadband photodetector is demonstrated with an inorganic perovskite CsPbBr3 /GeSn heterojunction. The detection range can be covered from 450 to 2200 nm, and the responsivity of the heterojunction device is 4.92 times larger than that of a GeSn one under illuminated light of 532 nm, and also the device is showing good stability.